2001
DOI: 10.1002/mcs.10008
|View full text |Cite
|
Sign up to set email alerts
|

Relationships for modeling the performance of rectangular gas chromatographic columns

Abstract: Golay's theory for open tubular GC columns was recently revised for application to rectangular GC columns. The HETP was found to be the same as for open tubular columns provided the average linear velocity, u, and the resistanceto-mass-transfer-in-the-gas-phase, C , are redefined. In this paper, a simplified M expression for the average linear velocity is derived and used to fit a variety of exit flow data collected on microfabricated rectangular GC columns. Also the resistance-to-mass-transfer-in-the-gas-phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 20 publications
1
45
0
Order By: Relevance
“…(11) have been reported that rely on different approximations or boundary conditions [25][26][27][28][29][30][31][32][33]. It has been shown that additional contributions to HETP are generated at the side-walls of rectangular channels when these channels have a finite width [25][26][27][28][29][30][31][32][33].…”
Section: Theoretical Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…(11) have been reported that rely on different approximations or boundary conditions [25][26][27][28][29][30][31][32][33]. It has been shown that additional contributions to HETP are generated at the side-walls of rectangular channels when these channels have a finite width [25][26][27][28][29][30][31][32][33].…”
Section: Theoretical Sectionmentioning
confidence: 99%
“…Therefore, Eq. (11) holds for a rectangular channel of very large aspect ratio (parallel-plate or slab geometry: w h), and not for a square column (w = h) as suggested recently [26,33]. It should also be mentioned that Golay's theory does not apply to the domain of very high flow velocities since the derivation neglects any higher order terms [16].…”
Section: Theoretical Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…26,27 Low flow resistance resulting from the channel profile also facilitates high volumetric flow rate, which makes it possible that the channel length can be further increased without excessively increasing the injection pressure for maintaining reasonable fluidic flow rate and analysis time. 5 HAR channels are generally micromachined in a vertical paradigm to have a high density of channels per unit area on a chip and therefore provide a long vertically-accumulated absorption path length for optical detection.…”
Section: Fabrication Of High-aspect-ratio Quasi-rectangular Channelsmentioning
confidence: 99%
“…In recent years columns of rectangular, or nearly rectangular cross section have been used in micro-fabricated GC columns. Several authors have analyzed GC columns with rectangular cross sections [8,14,5,6,1,10]. However, all of these authors have assumed that the cross sections are uniformly coated with a thin layer of stationary phase.…”
Section: Introductionmentioning
confidence: 99%